Huntington Beach Miscellaneous (Antique Maytag, Rose O'Reilly's Home, Pier - Watkins, Howard::::::::: (1989)
Robin Watkins wearing dark sunglasses on front yard at Rose O'Reilly's home at 10952 Tonga Lane, Huntington Beach